The Role of Fiscal Decentralization on Inequality: Evidence from Papua Province - Fitra Pasapawidya Purna; Putri Hardiningsih; Mahrus Lutfi Adi Kurniawan; Lestari Sukarniati; Stanislaw Flejterski (JAMPE (Journal of Asset Management and Public Economy), 2026)
High income inequality is generally accompanied by unequal access to education, job training, and business opportunities, limitingemployment opportunities for the poor. One approach that can be applied to resolve this problem is by implementing a fiscal decentralization policy. Papua is one of the regions categorized as 3T (Underdeveloped, Frontier, and Outermost). This condition indicates serious challenges in development in Papua, especially in the aspects of basic infrastructure and fiscal independence. The main contribution of the study is to analyze the role of fiscal decentralization on development in Papua province. Fiscal decentralization plays an important role in promoting regional development, particularly in disadvantaged areas. The study used a panel data approach that combines time-series data (2019-2023) and cross-sectional data (29 regencies and cities) in Papua Province. The results of the study indicate that fiscal decentralization through the General Allocation Fund (DAU) and Special Allocation Fund (DAK) has no effect in reducing inequality rates in Papua Province. It isdue to geographical challenges and the unconditional transfer nature of DAU and DAK. In this case, DAU is mostly used for regional routine expenditures, while the DAK has a long-term effect on infrastructure development, which is the major obstacle in reducing inequality in Papua. This research implies that local governments need to improve the effectiveness of DAU and DAK utilization by prioritizing productive sectors.